MANAGING THE DEVELOPMENT OF SOCIO-ECONOMIC SYSTEMS - Nurmamatova Sevara Kamol qizi; Ruzmetova Diana Komilovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT The advancement of socio-economic systems demands thorough management strategies that incorporate economic, social, technological, and institutional elements. This article explores the characteristics of socio-economic systems, the principles guiding their management, and modern methods that promote sustainable development. It also highlights significant challenges and provides suggestions for improving management processes in today’s world.